Gambaran Gambaran Faktor Predisposing, Enabling Dan Reinforcing Pencegahan Penyakit DBD di Kelurahan Mautapaga - Tokan, Pius Kopong; Owa, Krispina; Ahmad, Hamsir (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Mautapaga Village is an area with a high level of DHF endemicity. The study aims to describe the predisposing, enabling and reinforcing factors related to the prevention of DHF. Descriptive research design, located in RT 07, 08, 29, 30 Mautapaga Village, research variables related to predisposing, enabling, and reinforcing factors. Population 140 families, simple sampling technique with consideration of similar characteristics. The sample was calculated using the Slovin formula with a 95% confidence level, a total sample of 103 people. Data collection using a questionnaire that has been tested for validity. The researcher began by explaining the inclusion criteria, benefits and objectives. Prospective respondents who were willing to fill out the informed consent, continued with interviews and observations. Data processing began with editing, coding. Univariate data analysis to describe the phenomenon and the magnitude of the problem of each component, presented in the form of a frequency distribution table. Results: generally education level ≥ high school (61.2%), unemployed (64.1%). Lack of knowledge (85.4%), negative attitude (75.7%), not sure (69.9%), low assessment (79.6%). This is the trigger for negative behavior in preventing DHF, 76.7% do not practice DHF prevention. Supporting factors in the form of the availability of Abate obtained from health centers (84.5%), however, 97.1% have less access to information. Likewise, 77.7% admitted to not getting enough support from others, the greatest support is health workers (66%). Conclusion: The level of knowledge about DHF is still low, as are attitudes, beliefs, and prevention behavior. Lack of awareness to provide supporting facilities and infrastructure for prevention measures, most get abate from health centers, as well as the lack of independence in accessing information about DHF. Support from other parties in preventing DHF, the largest from health centers. It is recommended that various parties can contribute to increasing public understanding of DHF, motivating them to continue to practice prevention. Keywords: Predisposing; Enabling; Reinforcing; DHF